Reaching the Rural Poor : A Renewed Strategy for Rural Development - World Bank (Washington, DC, 2013)
"From Vision to Action", the Bank's previous rural development strategy launched in 1997, had a decisive influence on global thinking - but disappointing results on the ground. In 2001, lending for agricultural projects was the lowest in the Bank's history. The new strategy is results oriented: "Reaching the Rural Poor" stresses practice, implementation, monitoring, and empowerment of the people it is designed to help. This strategy responds to changes in: the global environment; in client countries; and, in the Bank, starting with the development of regional action plans, and extensive consultations at the regional level. It also reflects, and reinforces the Bank's commitment to the United Nations Millennium Development Goals to increase rural incomes, and broaden opportunities for rural people. The key features of this strategy are to: focus on the rural poor; foster broad-based economic growth; address rural areas comprehensively; forge alliances of all stakeholders; and, address the impact of global developments on client countries. In this capacity, support for better agricultural, and trade policies, should be achieved through increased advocacy for trade liberalization, by mainstreaming agricultural trade liberalization, and trade-capacity development in the Bank's country assistance, and operations; and, by facilitating capacity building through technical assistance in the areas of standards, and sanitary and phytosanitary regulations.